1992
DOI: 10.1159/000126176
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of a Neurotransmitter Pathway Regulating the in vivo Release of Prolactin

Abstract: Nicotinic cholinergic, opiate and serotonergic agonists as well as dopaminer-gic antagonists induce the release of pituitary prolactin. The purposes of the present studies were to determine if nicotine, morphine and the serotonin 1A (5-HT1A) agonist 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) utilize a common synaptic pathway to release prolactin and, if so, to establish the serial order of the receptors involved. We also sought to determine whether the pathway under investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The demonstration of enhanced PRL secretion ln response to fleslnoxan ls consistent wlth earller reports that 8-0H-DPAT ellclts PRL release ln rats (Stmonovlc et al 1984;Willoughby et al 1988;Aulakh et al 1988;Dl Sclullo et al 1990;Kellar et al 1992;Flores et al 1992), whlch ls blocked by methyserglde or metergoline (Willoughby et al 1988;Aulakh et al 1988;Kellar et al 1992). In hllmans, lncreased PRL secr~tion was reported wlth busplrone (Meltzer et al 1983;Coccaro et al 1990;Anderson and Cowen, 1992), geplrone ), but no: wlth lpsaplrone (Lesch et al 1989) or tandosplrone (Miller et al 1990).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The demonstration of enhanced PRL secretion ln response to fleslnoxan ls consistent wlth earller reports that 8-0H-DPAT ellclts PRL release ln rats (Stmonovlc et al 1984;Willoughby et al 1988;Aulakh et al 1988;Dl Sclullo et al 1990;Kellar et al 1992;Flores et al 1992), whlch ls blocked by methyserglde or metergoline (Willoughby et al 1988;Aulakh et al 1988;Kellar et al 1992). In hllmans, lncreased PRL secr~tion was reported wlth busplrone (Meltzer et al 1983;Coccaro et al 1990;Anderson and Cowen, 1992), geplrone ), but no: wlth lpsaplrone (Lesch et al 1989) or tandosplrone (Miller et al 1990).…”
supporting
confidence: 78%
“…The 8-0H-DPAT administration induced PRL release (Slmonovic et al 1984;Willoughby et al 1988;Aulakh et al 1988;Di Sciullo et al 1990;Kellar et al 1992;Flores et al 1992). The effect of 8-0H-DPAT most likely involves 5-HT pathways since pretreatment with • methysergide or metergoline blocked the 8-0H-DPAT-induced PRL release (Willoughby et al 1988;Kellar et al 1992;Jorgensen et al 1993;Flores et al 1992) while these antagonists failed to attenuaie the PRL secretion induced by the DA antagonist haloperidol Ellis et al 1991). In addition.…”
Section: Assessment Of 5-htia Receptor Funetion In Animaismentioning
confidence: 99%
“…At the time of the increase in dopamine, an increase in plasma fenfluramine and norfenfluramine levels and prolactin concentrations was observed. It has been hypothesized that the ability of fenfluramine to release prolactin is indicative of an interaction between serotonin and dopamine (31). However, serotonin may also stimulate prolactin release directly (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although the stimulatory effect of serotonin on prolactin secretion is well documented [28], there are evidences that, under certain physiological or experimental conditions, activation of the serotoninergic system can also inhibit prolactin secretion, particularly at the end of pregnancy [4, 30, 31, 32, 33]. Previous studies reported that opioids increase the 5-HT turnover in the hypothalamus [68]and that stimulation of prolactin release depends upon intact serotoninergic neurotransmission [69, 70]. Moreover, immunocytochemical studies have shown that serotoninergic endings make synaptic contacts with POMC neurons in the arcuate nucleus [71].…”
Section: Discussionmentioning
confidence: 99%